Luria’s Syndrome for Neuropsychological Rehabilitation of Adolescents - Solovieva, Y; Quintanar, L (KnE Life Sciences, 2018)
Neuropsychology, as a science, studies possible relations between psychological processes and brain in cases of normality and diverse pathologies. Such kind of relations might be established and understood by different manners. A.R. Luria proposed unique and particular way of approach by brain units. Such conception is not completely understood and even less used in practice of diagnosis and rehabilitation today. Neuropsychologists provide assessments of isolated functions by help of psychometric procedures. The judgment of diagnosis refers to such terms as “attention or memory disorders”, dyslexia and so on. All these terms are really far away from the conception of systemic and dynamic representation of human actions in functional brain systems. Same or worse is the situation with rehabilitation directed to isolated operations as conductive exercises for isolated functions. The objective of our report is to share opinion of application of Luria’s methodology of syndrome analysis. Procedures of systemic functional diagnosis must conduct to systemic procedures in rehabilitation. An example of qualitative assessment of adolescent patient with brain injury is presented. Goals, stages and examples of formation of actions in rehabilitation with results are provided. Psychological conceptions of stage by stage formation and orientation base of action and its usage for rehabilitation is taken into account. We conclude that systemic and dynamic approach in neuropsychology might be conducted in reality of assessment and rehabilitation. We discuss the necessity of establishment of bridges between psychological theory of actions instead of functions and systemic representation of actions by functional brain systems. Keywords: neuropsychological rehabilitation, concepts of neuropsychology, functional diagnosis, qualitative neuropsychology, brain injury rehabilitation.